Myriad Philosophical Methodologies. (October 2016) - Rush, Penelope A.
Abstract: This article offers an overview of philosophical methodologies. In an attempt to avoid a certain circularity, the article itself tries to avoid consciously or solely deploying and engaging with any current standard notion of what constitutes a philosophical method or philosophy itself. It hopes to find some of the possible places in which philosophy occurs, and this turns out to include (at least) such endeavours as literature, art, poetry, and linguistics. From here it considers how almost anything—for example, conversation, everyday life, and love—can also be philosophy. An attempt is made to identify some characteristic feature of philosophy as it occurs in all such forms. In the end, the simultaneous enacting of a peculiar optimism and particular humility both, in the search for knowledge, is put forward as potentially sufficient to at least begin to identify philosophy across its many guises.